Strategi Pemasaran Online Pada Martabak Kubang Dalam Rangka Meningkatkan Usaha UMKM Pada Saat New Normal - Hayu Yolanda Utami; Syailendra Eka Saputra (XXXXX, 2023)
Online Marketing Strategies such as promotion via website and blogs. With this media traders can sell within 24 hours. On the web, merchants can explain in detail the product and services being sold. Therefore, it is necessary to have special abilities from business actors to be able to compete so that they can increase their sales. The purpose of this community service activity is to overcome partner problem, namely how online marketing strategies can increase sales of Martabak Kubang in Bukittinggi during the new normal era. The method used in the implementation of Online Marketing Strategies is in the form of presentation. The results obtained from the implementation of Online Marketing Strategies in increase sales through online marketing and be able to compete with other small and medium enterprises.